Urban pipe smoking tradition in a soldier’s ethos. Archaeological finds of accessories for smoking in the context of soldiers stationed at Wawel in Cracow - Puziuk, Jakub (City and War, 2021)
Tobacco smoking for soldiers in the modern period was not only a relaxing function, but also a specific therapeutic therapy. This plant has long been perceived through the prism of a therapeutic herb (herba panacea) recommended as a universal medical preparation. The culture of smoking tobacco in a pipe has achieved a high degree of development, especially in the Habsburg Empire and the later Austro-Hungarian state, which can be confirmed by archaeological finds of utensils related to this period. Interpretation of the historical context of such sources very often indicates that their users were the military community, which, especially during the Austro-Hungarian domination, was stationed in large numbers in an extensive network of forts and barracks, often located in urban areas. Krakow was an example of such an urban center, being one of the key military bases. The most important point of defense of the fortress built in Krakow was the Wawel Hill, which in 1848 was officially transferred to the barracks for Austrian troops. Archaeological research carried out at Wawel in the years 1948–2011 led to the discovery of the most numerous collection of modern pipes in Lesser Poland. The most magnificent are the finds of stub-stemmed pipes and porcelain utensils, which constitute the material trace of the presence of Austrian and Austro-Hungarian troops in the 19th century and at the beginning of the 20th century. These works prove that among the soldiers stationed at Wawel, high-quality marked pipe bowls, produced in various workshops operating in the countries of the Habsburg Empire and later Austro-Hungary, were very popular. The soldiers indulged in tobacco smoking also in another variant of bowls, which is known as the Café-type pipe. The appearance of this type of accessories was related to the 19th century fashion, popular especially among the burghers of Central Europe, which popularized the so-called „Café culture”, which consists in spending free time drinking coffee and smoking pipes in city cafes. Porcelain pipes are also present in the assortment of 19th century smoking accessories used by soldiers. Their characteristic remains are porcelain bowls and water bags made of the same material. With a high degree of probability, this type of utensils recognized at Wawel are fragments of the armorial pipes, which were given as souvenirs to soldiers leaving the service in the Krakow citadel. The remains of pipes identified in the context of soldiers stationed at Wawel Hill reflect the attachment of this community to the tobacco addiction, which was practiced in accessories referring to the Eastern European model of smoking. Tobacco was valued not only for its relaxation values, but also played an important role in the process of healing and mental rehabilitation of soldiers, as evidenced by the large number of finds of pipes in the areas of the buildings of the former garrison hospital. Moreover, the influence of the urban smoking culture is noticeable, which inspired the use of some customs and practices of spending free time with the pipe among soldiers, the best example of which are the discovery of Café-type pipes on the Wawel Hill.